Oral English language needs of police constables in a Crime Prevention Department / Madhavi Shilvaraj - Madhavi , Shilvaraj (2018)
This study was carried out to determine the Oral English Language Needs of Police Constables in a Crime Prevention Department of a district police station in Melaka. This study is based on a qualitative approach using interview data and frequency counts from a questionnaire. The questionnaire was completed by 10 police constables in the Crime Prevention Department. In addition, semi structured interviews were conducted with a senior police officer and 3 police constables to further verify the derived data. The findings revealed that Oral English language skills is essential for Malaysian police constables in the Crime Prevention Department when taking down statements from victims/suspects, interrogating suspects and when gathering evidence from the public, especially among tourists. Hence, they need to be proficient in speaking and listening to the public. However, most of them need training in Basic English conversation and grammar as they perceived themselves to be below average in their English proficiency, in particular the oral and listening skills. This is an indication that both oral and listening skills need to be emphasized in the proposed English for Specific Purposes (ESP) course. Based on the findings, a course was designed to meet their oral communication needs. A successful ESP course would enable the police constables to perform their duties better, ease their job when dealing with foreign nationals and give them more confidence in communicating in English. Although all necessary precautions were taken while conducting this study, sample size has been the major limitation. Therefore, a larger sample is recommended for future research.